Strengthening School Management with Digital Education Technology to Improve the Quality of Educational Output - Leni Maryani; Jumaidi Nur; Sri Utami; Ihfa Indira Nurnaifah; Farida (Indonesian Journal Of Educational Research and Review, 2023)
Digital educational technologies enhance teaching methodologies through multimedia resources, interactive simulations and real-time assessment tools. Teachers can leverage adaptive learning algorithms to adapt learning to the individual needs of students, driving engagement, understanding, and academic success. Moreover, data-driven decision-making is facilitated by digital educational technologies. Educators gain valuable insights into student performance through sophisticated analytics, enabling them to identify areas for improvement and implement targeted interventions. This approach supports early identification of at-risk students and ensures that a comprehensive support system is in place. In addition, digital education technologies promote collaboration and communication between various stakeholders, including teachers, students, parents and administrators. This enables real-time feedback, collaboration between parents and teachers, and remote learning opportunities, creating a participatory and dynamic educational environment. In conclusion, embracing digital education technology has great potential to strengthen school management and meet the demands of 21st century quality education. By automating administrative tasks, improving teaching methodologies, enabling data-driven decision-making and promoting collaboration, educational institutions can adapt to evolving challenges and deliver high-quality educational outcomes. Embracing these technological advances is important for preparing students for the demands of the digital age and ensuring a successful future.